Expression of the Trait of Adaptability in the Organizational Culture of Lithuanian General Education Schools - Starkutė, Jovita (Acta Paedagogica Vilnensia, 2024)
In the context of organizational culture, in order for organizations to be adaptive, to develop adaptability in daily activities, it becomes important to look for solutions on how to systematically adapt to constantly changing conditions in the organization and help organizations to become more adaptive. However, it is not easy, and it becomes a problem, because adaptability in educational institutions is systemic and it is one of the processes of organizational culture. Therefore, the aim of the article is to reveal the expression of the trait of adaptability and its constituent indicators (creating change, organizational learning and customer focus) in the study of organizational culture in general education schools based on the internationally recognized Denison Organizational Culture Survey (DOCS). The results of the study revealed that educational institutions of Lithuania pay great attention to organizational learning, however, there are challenges in the creating change and customer focus fields of organizational culture.